Keeping Things Positive: Affect as a Mediator between Physical Activity and Psychological Functioning - Aliakbar Foroughi; Nils T. Henschel; Hassan Shahi; Scott S. Hall; Lawrence S. Meyers; Kheirollah Sadeghi; Aliakbar Parvizifard; Klaus Boehnke; Serge Brand (MDPI AG, 2023)
Higher physical activity is generally associated with more favorable psychological functioning. However, the role of positive and negative affect in such associations is unclear. Accordingly, this cross-sectional study explored whether affect mediated the relationship of physical activity with psychological well-being (PWB) and psychological dysfunctioning (PD). Young Iranian adults (N = 200) completed self-rating questionnaires covering physical activity, positive and negative affect, and proxies of PWB and PD. Regression analyses indicated that higher physical activity levels and higher positive and lower negative affect predicted proxies of PWB. The same (albeit in the opposite direction) applied to proxies of PD. Structural equation modeling indicated that positive and negative affect mediated the relationship between physical activity and PWB/PD. Accordingly, change in affect might be an important mechanism behind the association of physical activity and PWB/PD. Future research should further explore this across target populations and cultural contexts. Longitudinal and/or experimental studies are needed to disentangle causality.